Merits of Kerrisons punch over powered drill in endonasal DCR - Sheikh, Shahnaz; Vaze, Vikrant Vilas; Bajaj, Anushree; ., Bhalachandra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: DCR is an operation used to treat nasolacrimal duct obstruction. Various types of DCR are conventional, endonasal/endoscopic DCR and endolaser DCR. Several modalities like Kerrison punch and powered drill are used in endoscopic DCR to improve success rate, reduce complications and shorten operative time. Aim of the study were, to compare the advantages of non powered Kerrison punch over powered drill regarding time in endoscopic DCR and to compare the advantages of non powered Kerrison punch over powered drill regarding complication rate in endoscopic DCR Methods: The study was carried out at ENT department of Dr. Ulhas Patil Medical College and hospital Jalgaon from March 2017 to July 2018. Total of 61 patients were included in the study (35 Kerrison punch and 33 drill). Results: A total of 68 endoscopic DCRs. Procedure success rate among Kerrison punch group was 88.00% vs 91% in drill group. The complications for both groups were statistically not significant(P=0.91).The mean operating time among Kerrison punch group was significantly lower than in drill group 80 vs. 135 min (P=0.0001). Conclusions: Kerrison punch showed significant reduction in operating time when compared to drill for endoscopic DCR. No statistically significant difference was found between both groups regarding procedures, success rate and complications.